Azobioisosteres of Curcumin with Pronounced Activity against Amyloid Aggregation, Intracellular Oxidative Stress, and Neuroinflammation. Issue 19 (5th March 2021) - Hofmann, Julian; Ginex, Tiziana; Espargaró, Alba; Scheiner, Matthias; Gunesch, Sandra; Aragó, Marc; Stigloher, Christian; Sabaté, Raimon; Luque, F. Javier; Decker, Michael
Abstract: Many (poly‐)phenolic natural products, for example, curcumin and taxifolin, have been studied for their activity against specific hallmarks of neurodegeneration, such as amyloid‐β 42 (Aβ42) aggregation and neuroinflammation. Due to their drawbacks, arising from poor pharmacokinetics, rapid metabolism, and even instability in aqueous medium, the biological activity of azobenzene compounds carrying a pharmacophoric catechol group, which have been designed as bioisoteres of curcumin has been examined. Molecular simulations reveal the ability of these compounds to form a hydrophobic cluster with Aβ42, which adopts different folds, affecting the propensity to populate fibril‐like conformations. Furthermore, the curcumin bioisosteres exceeded the parent compound in activity against Aβ42 aggregation inhibition, glutamate‐induced intracellular oxidative stress in HT22 cells, and neuroinflammation in microglial BV‐2 cells. The most active compound prevented apoptosis of HT22 cells at a concentration of 2.5 μm (83 % cell survival), whereas curcumin only showed very low protection at 10 μm (21 % cell survival). Abstract : Improving on nature : Synthetic bioisosteres of the natural product curcumin are designed, synthesized, and computationally evaluated by molecular dynamics and replica‐exchange molecular dynamics simulations for their interaction with amyloid‐β 42 aggregation. Biological evaluation shows that such compounds greatly exceed the anti‐neuroinflammatory and neuroprotective properties of their parent compounds.